ANALISIS HUKUM TERHADAP VONIS BEBAS TERDAKWA KASUS KORUPSI OLEH MAJELIS HAKIM DI PENGADILAN NEGERI POHUWATO - Muh. Nasir (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2011)
Key issues that dikemukkakan in this study is to know the basic considerations Pohuwato District Court Judge in imposing sentence is free from all charges in a case of criminal corruption, as well as to determine and analyze the factors - factors that influence the birth of an acquittal verdict of all charges in a case of follow-corruption in the District Court Pohuwato. Research results indicate that the District Court Judge Pohuwato in handling corruption cases required an increase in HR and has a High Morale, so there is no more corruption cases in the future in a verdict free from any claims Law Judge in order to maintain credibility and maintain the trust of the community.